On injectors of finite groups - Liu, Shitian; Zhang, Runshi (Armenian Journal of Mathematics, 2010)
If F is a non-empty Fitting class, π=π(F) and G a group such that every chief factor of G/G_F is an C_π^s-group. Then G has at least one F-injector. This result is used to resolve an open problem and generalize some known results.